Sexual Education and Teacher Candidates' Attitudes Towards Sexuality - Gursimsek, Isik (Cambridge Univ Press, 2010)
The aim of this study is to investigate teacher candidates' attitudes related to sexuality and homosexuality and to determine the relationship between these attitudes and course attendance, gender and cultural background. The sample or the study consist of teacher candidates that have (n = 302) and have not (a = 176) attended the sexual education course during the 2006-2007 academic year at a faculty of education in Izmir - a city in the western coastal region of Turkey. The Sexual Attitude Scale (SAS) and the Homosexuality Attitude Scale (HAS) were used to gather data at pre-test and post-test levels. Results demonstrate that sexuality education has a positive effect on participants' attitudes towards sexuality. In contrast, the course does not have any influence on candidates approach to homosexuality.
Keywords: sexual education; sexuality; homosexuality; teacher attitudes; teacher training